Pengaruh Harga, Lokasi, Suasana Toko (Store Atmosphere) terhadap Keputusan Pembelian : Studi pada Konsumen Koffiekopi Kota Jambi - Agnes Ayu Arianda; Rafidah Rafidah; Muhammad Orinaldi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to analyze the influence of price, location and store atmosphere on consumer purchasing decisions for Koffie Kopi in Jambi City. This type of research is quantitative. The data source for this research is primary data by taking a sample of Koffie Kopi customers in Jambi City. Data collection was carried out among 96 respondents who were Koffie Kopi Jambi City customers. This research uses multiple regression analysis methods. The findings from this research show that: 1. Price has a significant influence on the purchasing decision process of Jambi City Koffie Coffee consumers, 2. Location has a significant influence on the Jambi City Koffie Coffee consumer purchasing decision process, 3. Store Atmosphere has a significant effect on the process Jambi City Coffee Koffie consumer purchasing decisions.